21.4: Invited Paper: Near‐to‐Eye Display Application Based on Digital Electro‐optics Platform (X‐on‐Silicon). (28th November 2018) - Tsai, Chun-Wei
Abstract : Digital Electro‐optics Platform is the main concept of Jasper Display Corp. (JDC) to develop various applications. These applications are based on our X‐on‐Silicon technologies, for example, X‐on‐Silicon technologies could be used on Liquid Crystal on Silicon (LCoS), Micro Light‐Emitting Diode on Silicon (pLEDoS), Organic Light‐Emitting Diode on Silicon (OLEDoS), and Cell on Silicon (CELLoS), etc. In this paper, we provide novel concepts and real cases for near‐to‐eye applications based on phase‐only LCoS‐SLM and μLEDoS, such as holographic near‐to‐eye displays and focal surface displays.